Emerging citizen responses to disasters in Germany. Disaster myths as an impediment for a collaboration of unaffiliated responders and professional rescue forces. (14th September 2017) - Lorenz, Daniel F.; Schulze, Katja; Voss, Martin
Abstract : Combating disasters necessitates taking advantage of all means and resources that are available. A number of events in recent years have demonstrated the necessity, as well as the potential of well‐integrated and coordinated action between unaffiliated and professional responders. Nevertheless, in practical situations this potential remains largely untapped. This article investigates the case in Germany and asks to which extent known and researched disaster myths impede the cooperation between unaffiliated and professional responders. We combine data from observations of a full‐scale exercise, a representative population survey ( N  = 1.006), and expert interviews with professional rescue workers to answer our research question. With the results of our research, we have deduced that these disaster myths still significantly influence the perceptions and practical actions of the various involved actors and, as such, that approaches aiming to improve the various forms of cooperation between all available forces must take these underlying assumptions into account.